Severe Vitamin D Deficiency is Associated with Mortality Risk in Critically Ill Patients with Acute Kidney Injury - Shen B; Liu B; Wang Y; Wang R; Gu D (International Journal of General Medicine)
Beili Shen, Bianling Liu, Yanhui Wang, Rui Wang, Dongfeng Gu The Fifth Clinical Medical College of Henan University of Chinese Medicine (Zhengzhou People’s Hospital), Zhengzhou, Henan, 450003, People’s Republic of ChinaCorrespondence: Dongfeng Gu, Department of Nephrology, The Fifth Clinical Medical College of Henan University of Chinese Medicine (Zhengzhou People’s Hospital), No. 33 Huanghe Road, Zhengzhou, Henan, 450003, People’s Republic of China, Tel +86-371-67077643, Email gudongfengzz@163.comPurpose: Deficiency in vitamin D is associated with adverse outcomes in several health conditions. However, the specific impact of vitamin D levels on mortality in acute kidney injury (AKI) patients remains inadequately explored. This study aims to investigate the association between serum vitamin D concentrations and mortality risk in critically ill patients diagnosed with AKI. We hypothesize that severe vitamin D deficiency is associated with an increased risk of 90-day all-cause mortality in these patients.Patients and Methods: This study retrospectively enrolled 259 adult AKI patients admitted to the intensive care unit (ICU) at The Fifth Clinical Medical College of Henan University of Chinese Medicine (Zhengzhou People’s Hospital) between July 2021 and June 2023. Based on 25-hydroxyvitamin D (25-OHD) levels, they were categorized into 4 groups: severe deficiency (< 10 ng/mL), deficiency (10– 20 ng/mL), insufficiency (20– 30 ng/mL), and sufficiency (> 30 ng/mL). Multivariate survival analysis using Cox’s regression model was used to analyze the impact of vitamin D concentrations on the 90-day all-cause mortality risk after controlling for potential confounders.Results: The 90-day all-cause mortality rate was the highest in patients with severe deficiency (50.8%), followed by those with deficiency (35.0%), insufficiency (23.9%), and sufficiency (12.2%). Multivariate Cox regression showed that compared with sufficiency, severe deficiency (HR=3.34, 95% CI: 1.14– 9.77; P=0.03) was independently associated with a higher risk of 90-day all-cause mortality, but deficiency and insufficiency were not significantly associated with 90-day all-cause mortality risk.Conclusion: Severe vitamin D deficiency (< 10 ng/mL) significantly increases the risk of mortality in AKI patients, underlining the need for monitoring and potentially supplementing vitamin D in this population.Keywords: acute kidney injury, vitamin D deficiency, mortality, prognosis